KARAKTERISTIK KEMAMPUAN BERPIKIR SPASIAL SISWA BERDASARKAN KEMAMPUAN MATEMATIKA DALAM PEMBELAJARAN GEOGEBRA BERBASIS ETNOMATEMATIKA GUDANG ATAG - Ziefa Fitria Noviyanti Thifal Rif’at; Erfan Yudianto; Lela Nur Safrida; Susanto Susanto; Robiatul Adawiyah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2025)
Students frequently demonstrate different spatial thinking characteristics despite experiencing the same geometry learning environment. However, limited attention has been given to how these characteristics vary according to students' mathematical ability. This study aimed to describe students' spatial thinking characteristics based on mathematical ability in GeoGebra-supported ethnomathematics learning using the Gudang Atag context. A qualitative descriptive approach was employed involving 31 eighth-grade students from a junior high school in Jember, Indonesia. Based on their mathematics achievement, students were classified into high, moderate, and low mathematical ability groups. One representative student from each group was selected for in-depth analysis through a spatial thinking test and semi-structured interviews. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while data credibility was established through technique triangulation. The findings revealed distinct spatial thinking characteristics across the three mathematical ability groups. Students with high mathematical ability demonstrated accurate spatial visualization, orientation, and spatial relations, whereas students with moderate mathematical ability were able to perform these aspects but still relied on GeoGebra to confirm their visual representations. In contrast, students with low mathematical ability depended heavily on GeoGebra to recognize object structures and experienced difficulties in constructing stable mental representations of spatial relationships. These findings indicate that mathematical ability shapes students' spatial thinking characteristics even when they participate in the same learning environment. The study provides empirical evidence that can support teachers in designing geometry instruction that accommodates students' diverse spatial thinking characteristics